THE EFFECT OF TAX COLLECTORS, TAXPAYER AWARENESS, AND TAX SANCTIONS ON TAXPAYER COMPLIANCE - Willy Nurhayadi; Ariawan Rahmat; Desty Indrawati Subroto (SEAN Institute, 2022)
Banten Province is a significant business attraction. Some of the factors are the strategic position of Banten Province close to the capital city of Jakarta and the inter-island link in trade and logistics delivery, as for others, significant infrastructure growth, as well as the attractiveness of investment and the significant growth of Micro, Small and Medium Enterprises (MSMEs) until their products have been exported abroad. Thus, the Banten Provincial government seeks to maximize regional revenues and help state revenues for sustainable development, especially the community's welfare.The realization of MSME tax revenues has not been optimal, even slowing down in 2021. This study aims to find out the extent of tax knowledge for MSME actors and taxpayer awareness of MSME actors which has an impact on the compliance of MSME actors in paying taxes, as well as whether with the tax sanctions rules, MSME actors in Banten Province will comply with their obligations as taxpayers, so that MSME taxpayers in Banten Province can make a significant contribution to state income through the type of MSME income tax. It is hoped that this research can increase the knowledge and awareness of MSME taxpayers in paying taxes to avoid tax sanctions, and also impact state revenues.This study describes the level of tax knowledge and awareness of MSME taxpayers towards taxpayer compliance, as well as the extent to which MSME actors can avoid tax sanctions so that MSME actors can comply with paying taxes. This stage of research consists of preparing a research design, determining the location, and the subject to be studied, field studies through presurvey activities, collecting supporting data, analyzing data, and drawing conclusions on the data that has been analyzed.